Labor Insertion and Educational Inclusion of Young People with Hearing Impairment in Chincha Alta - Vásquez León, Shirley Mirella (2021)
Labor insertion and educational inclusion is a problem that affects young people with disabilities as it intermingles two social situations: exclusion and discrimination. This paper aimed to calculate the degree of relationship between educational inclusion and job placement in a post-adolescent population affected by hearing loss in Chincha Alta. A descriptive-correlational study was designed with a sample of 106 young people who have a hearing impairment in the Chincha Alta district in Ica, to whom two instruments were applied to assess educational inclusion and job placement. The results show that there is a moderately high relationship, being significant, between the variables educational inclusion and labor insertion of people who are affected in their hearing potential. It is concluded that educational inclusion is significantly related to the employment aspect of people with decreased hearing in Chincha Alta during 2019.